Identification of Two Dysfunctional Variants in the ABCG2 Urate Transporter Associated with Pediatric-Onset of Familial Hyperuricemia and Early-Onset Gout - Toyoda, Yu; Pavelcová, Kateřina; Bohatá, Jana; Ješina, Pavel; Kubota, Yu; Suzuki, Hiroshi; Takada, Tappei; Stiburkova, Blanka (International journal of molecular sciences, 2021)
The ABCG2 gene is a well-established hyperuricemia/gout risk locus encoding a urate transporter that plays a crucial role in renal and intestinal urate excretion. Hitherto, p.Q141K-a common variant of ABCG2 exhibiting approximately one half the cellular function compared to the wild-type-has been reportedly associated with early-onset gout in some populations. However, compared with adult-onset gout, little clinical information is available regarding the association of other uricemia-associated genetic variations with early-onset gout; the latent involvement of ABCG2 in the development of this disease requires further evidence. We describe a representative case of familial pediatric-onset hyperuricemia and early-onset gout associated with a dysfunctional ABCG2, i.e., a clinical history of three generations of one Czech family with biochemical and molecular genetic findings. Hyperuricemia was defined as serum uric acid (SUA) concentrations 420 μmol/L for men or 360 μmol/L for women and children under 15 years on two measurements, performed at least four weeks apart. The proband was a 12-year-old girl of Roma ethnicity, whose SUA concentrations were 397-405 µmol/L. Sequencing analyses focusing on the coding region of ABCG2 identified two rare mutations-c.393G>T (p.M131I) and c.706C>T (p.R236X). Segregation analysis revealed a plausible link between these mutations and hyperuricemia and the gout phenotype in family relatives. Functional studies revealed that p.M131I and p.R236X were functionally deficient and null, respectively. Our findings illustrate why genetic factors affecting ABCG2 function should be routinely considered in clinical practice as part of a hyperuricemia/gout diagnosis, especially in pediatric-onset patients with a strong family history.
Keywords: Uric Acid; Polymorphism, Single Nucleotide; nádorové proteiny; Humans; ATP Binding Cassette Transporter, Subfamily G, Member 2; SUA-lowering therapy; ethnic specificity; dítě; Child; rare variant; jednonukleotidový polymorfismus; Female; mutace; clinico-genetic analysis; dospělí; hyperurikemie; Organic Anion Transporters; Phenotype; lidé; kyselina močová; HEK293 Cells; Roma; precision medicine; serum uric acid; dna (nemoc); Adult; transfekce; Pedigree; Gout; rodokmen; ženské pohlaví; Male; přenašeče organických aniontů; fenotyp; HEK293 buňky; genetická predispozice k nemoci; Genetic Predisposition to Disease; Czech Republic; Hyperuricemia; genetic variations; Transfection; Mutation; Česká republika; mužské pohlaví; Neoplasm Proteins; ABC transportér z rodiny G, člen 2; ABCG2 genotype; urate transporter